Handover Control for Human-Robot and Robot-Robot Collaboration - Costanzo, Marco; De Maria, Giuseppe; Natale, Ciro (Frontiers in Robotics and AI, 2021)
Modern scenarios in robotics involve human-robot collaboration or robot-robot cooperation in unstructured environments. In human-robot collaboration, the objective is to relieve humans from repetitive and wearing tasks. This is the case of a retail store, where the robot could help a clerk to refill a shelf or an elderly customer to pick an item from an uncomfortable location. In robot-robot cooperation, automated logistics scenarios, such as warehouses, distribution centers and supermarkets, often require repetitive and sequential pick and place tasks that can be executed more efficiently by exchanging objects between robots, provided that they are endowed with object handover ability. Use of a robot for passing objects is justified only if the handover operation is sufficiently intuitive for the involved humans, fluid and natural, with a speed comparable to that typical of a human-human object exchange. The approach proposed in this paper strongly relies on visual and haptic perception combined with suitable algorithms for controlling both robot motion{\color{red}, to allow the robot to adapt to human behaviour,} and grip force{\color{red}, to ensure a safe handover}. The control strategy combines model-based reactive control methods with an event-driven state machine encoding a human-inspired behaviour during a handover task{\color{red}, which involves both linear and torsional loads, without requiring explicit learning from human demonstration}. Experiments in a supermarket-like environment with humans and robots communicating only through haptic cues demonstrate the relevance of force/tactile feedback in accomplishing handover operations in a collaborative task.